2015
DOI: 10.1016/j.jcf.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Sputum club cell protein concentration is associated with pulmonary exacerbation in cystic fibrosis

Abstract: Background Cystic fibrosis (CF) patients exhibit a progressive decline in lung function accelerated by intermittent pulmonary exacerbations. There are urgent needs for clinically relevant biomarkers to aid in the diagnosis and management of a CF pulmonary exacerbation, in addition to providing insight into its pathophysiology. Club Cell Secretory Protein (CCSP) is produced by bronchial epithelial cells, known to have anti-inflammatory properties and may play a role in CF pulmonary exacerbations. Our objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…These proteins produced by Clara cells possess anti-inflammatory qualities. Previously it was observed that CCSP expression and production are decreased in chronic asthmatic patients [178] and decreased levels of CCSP in broncho-alvelolar lavage fluid were also found in CF patients [179]. Patients with mucoid P. aeruginosa variants also had a significantly lower CCSP concentration in sputum.…”
Section: Discussionmentioning
confidence: 95%
“…These proteins produced by Clara cells possess anti-inflammatory qualities. Previously it was observed that CCSP expression and production are decreased in chronic asthmatic patients [178] and decreased levels of CCSP in broncho-alvelolar lavage fluid were also found in CF patients [179]. Patients with mucoid P. aeruginosa variants also had a significantly lower CCSP concentration in sputum.…”
Section: Discussionmentioning
confidence: 95%
“…However, the levels did not return to normal despite intensive antibiotic treatment, hence negating their potential use as a marker of response to treatment [110]. Biomarkers that correlate to PA colonisation also include club cell secretory protein (CCSP), which is inversely related to the NE concentration in CF sputum and patients with pseudomonas aeruginosa have significantly lower CCSP than non-colonised individuals [112]. Furthermore, levels of leukotriene B4 (LTB4) correlate with PA colonisation in CF compared to other organisms [104].…”
Section: Sputum and Bronchoalveolar Lavage Fluid Biomarkersmentioning
confidence: 99%
“…Three biomarkers – desmosine, club cell secretory protein (CCSP) and cathepsin B have previously been associated with CF lung disease; however, their applicability to CF infants has not been investigated [ 10 18 ]. We have shown that sputum CCSP concentration was both higher in adults with CF in the outpatient setting compared to during a CF pulmonary exacerbation and negatively associated with sputum NE concentration [ 17 ]. CCSP is produced by bronchial epithelial cells and known to have anti-inflammatory properties and may reflect CF lung disease activity [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that sputum CCSP concentration was both higher in adults with CF in the outpatient setting compared to during a CF pulmonary exacerbation and negatively associated with sputum NE concentration [ 17 ]. CCSP is produced by bronchial epithelial cells and known to have anti-inflammatory properties and may reflect CF lung disease activity [ 17 ]. We have also shown that both sputum and urinary desmosine concentration decrease significantly during a CF pulmonary exacerbation [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%